2011
DOI: 10.1371/journal.pone.0015853
|View full text |Cite
|
Sign up to set email alerts
|

Ralstonia solanacearum Extracellular Polysaccharide Is a Specific Elicitor of Defense Responses in Wilt-Resistant Tomato Plants

Abstract: Ralstonia solanacearum, which causes bacterial wilt of diverse plants, produces copious extracellular polysaccharide (EPS), a major virulence factor. The function of EPS in wilt disease is uncertain. Leading hypotheses are that EPS physically obstructs plant water transport, or that EPS cloaks the bacterium from host plant recognition and subsequent defense. Tomato plants infected with R. solanacearum race 3 biovar 2 strain UW551 and tropical strain GMI1000 upregulated genes in both the ethylene (ET) and salic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(136 citation statements)
references
References 53 publications
3
128
0
3
Order By: Relevance
“…Bacterial wilt caused by Ralstonia solanacearum is contemplated to be one of the most important plant diseases in tropical agriculture [1] [2]. It has a large host range of more than 200 species in 50 families [3].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial wilt caused by Ralstonia solanacearum is contemplated to be one of the most important plant diseases in tropical agriculture [1] [2]. It has a large host range of more than 200 species in 50 families [3].…”
Section: Introductionmentioning
confidence: 99%
“…DC3000 derivative lacking the conserved effector locus instead of the wild type (not shown). Other studies have shown disparate responses of effector proteins on Arabidopsis and tomato plants (Lin et al 2008;Milling et al 2011). Unsurprisingly, Arabidopsis is a tremendous source of plant resistance toward pathogens and its study led to the discovery of the R protein, RRS1 (resistance to R. solanacearum 1) that confers resistance to R. solanacearum expressing PopP2 (Deslandes et al 2003).…”
Section: Awr Are Bona Fide T3ementioning
confidence: 99%
“…Bacterial wilt caused by R. solanacearum is deemed to be one of the most important plant diseases in tropical agriculture (Hayward, 1990;Milling et al, 2011). It has a large host range of more than 200 species in 50 families (Aliye et al, 2008).…”
Section: Introductionmentioning
confidence: 99%